Minimally Invasive Versus Open Distal Pancreatectomy (LEOPARD): A Multicenter Patient-blinded Randomized Controlled Trial. Issue 1 (January 2019) - de Rooij, Thijs; van Hilst, Jony; van Santvoort, Hjalmar; Boerma, Djamila; van den Boezem, Peter; Daams, Freek; van Dam, Ronald; Dejong, Cees; van Duyn, Eino; Dijkgraaf, Marcel; van Eijck, Casper; Festen, Sebastiaan; et al.
Abstract : Objective: This trial followed a structured nationwide training program in minimally invasive distal pancreatectomy (MIDP), according to the IDEAL framework for surgical innovation, and aimed to compare time to functional recovery after minimally invasive and open distal pancreatectomy (ODP). Background: MIDP is increasingly used and may enhance postoperative recovery as compared with ODP, but randomized studies are lacking. Methods: A multicenter patient-blinded randomized controlled superiority trial was performed in 14 centers between April 2015 and March 2017. Adult patients with left-sided pancreatic tumors confined to the pancreas without vascular involvement were randomly assigned (1:1) to undergo MIDP or ODP. Patients were blinded for type of surgery using a large abdominal dressing. The primary endpoint was time to functional recovery. Analysis was by intention to treat. This trial was registered with the Netherlands Trial Register (NTR5689). Results: Time to functional recovery was 4 days [interquartile range (IQR) 3–6) in 51 patients after MIDP versus 6 days (IQR 5–8) in 57 patients after ODP ( P < 0.001). The conversion rate of MIDP was 8%. Operative blood loss was less after MIDP (150 vs 400 mL; P < 0.001), whereas operative time was longer (217 vs 179 minutes; P = 0.005). The Clavien–Dindo grade ≥III complication rate was 25% versus 38% ( P = 0.21). Delayed gastric emptying grade B/C was seen less often after MIDP (6% vs 20%; P = 0.04). Postoperative pancreatic fistulas grade B/C were seen in 39% after MIDP versus 23% after ODP ( P = 0.07), without difference in percutaneous catheter drainage (22% vs 20%; P = 0.77). Quality of life (day 3–30) was better after MIDP as compared with ODP, and overall costs were non-significantly less after MIDP. No 90-day mortality was seen after MIDP versus 2% (n = 1) after ODP. Conclusions: In patients with left-sided pancreatic tumors confined to the pancreas, MIDP reduces time to functional recovery compared with ODP. Although the overall rate of complications was not reduced, MIDP was associated with less delayed gastric emptying and better quality of life without increasing costs. Abstract : Supplemental Digital Content is available in the text